Intestinal/uterine antispasmodics, sedative effects of Fuchsia magellanica Lam. leaves’ and flowers’ extracts and their flavonolic components - Bernal Ochoa, Ana María (2021)
Background: Fuchsia magellanica Lam. ( Onagraceae ) is a native plant of the Andean-Patagonian region, and it is also naturalized in Argentina and other parts of the world. Leaves are used for treating indigestion, stomachache, as sedative, for difficult delivery and as antiemmenagogue. However, up to now the pharmacological basis of such uses were not studied. Purpose: This work evaluates the gastrointestinal, uterine and sedative effects of leaves (L) and flowers (F) tinc- tures of F. magellanica from wild patagonian (T-Fm-P) and naturalized (T-Fm-BA) plants, as well as the mechanism of action and the flavonoids profile of both plants. Methods: Phytochemical studies were evaluated by using TLC and HPLC methodologies. The ex-vivo effects of T-Fm-BA and T-Fm-P were evaluated on contractile concentration-response curves (CRC) of carbachol (CCh) and calcium (Ca 2 + ) in rat isolated intestinal and uterine tissues. In vivo tests for intestinal transit, elevated cross plus-maze and open-field tests were performed in mice. Results: Wild and cultivated leaves and flowers ethanolic extracts induced antispasmodic effect, as a non- competitive inhibitor of the CCh-CRC in intestine, with IC 50 of 272.8 ± 64.3 μg/ml for T-L-Fm-P and 257.4 ± 36 μg/ml for T-L-Fm-BA. A similar effect was obtained in Ca 2 + -CRC with IC 50 of 152.9 ± 29.1 μg/ml and 138.4 ± 48.6 μg/ml respectively. Mice intestinal transit was reduced at oral doses of 73.5 mg/kg of T-L-Fm-P. In uterine tissues, both T-L-Fm reduced the contractions of CCh CRC´s as non-competitive antagonists, with IC 50 near those in intestine. The T-L-Fm-BA also inhibited the serotonin CRC´s and contribution of other relaxing mechanisms was investigated. Although extracts didn?t show anxiolytic effect in the elevated cross plus-maze test, they reduced the spontaneous activity of mice in the open-field at 32.7 mg/kg T-L-Fm-P and 41.7 mg/kg T-L-Fm-BA. Conclusions: Leaves and flowers ethanolic extracts from wild and cultivated plant F. magellanica showed intesti- nal and uterine antispasmodic effects, mainly by interfering with Ca 2 + influx. In mice, the ethanolic extracts reduced the intestinal transit and showed sedative effect. The effects agree with the presence of flavonoids, such as quercetin and kaempferol. This is the first study which gives experimental support for some of the traditional uses of F. magellanica .